THERMAL FLEXURAL ANALYSIS OF CROSS-PLY LAMINATED PLATES USING TRIGONOMETRIC SHEAR DEFORMATION THEORY - KULKARNI, SANJAY KANTRAO (2013)
A REFINED SHEAR DEFORMATION THEORY IS PRESENTED FOR THERMAL FLEXURAL ANALYSIS OF CROSS-PLY LAMINATED PLATES UNDER COMBINED LINEAR AND NONLINEAR THERMAL LOADS THROUGH THE THICKNESS OF LAMINATED PLATES. THE IN-PLANE DISPLACEMENT FIELD USES SINUSOIDAL FUNCTION IN TERMS OF THICKNESS CO-ORDINATE TO INCLUDE THE SHEAR DEFORMATION EFFECT. THE THEORY SATISFIES THE SHEAR STRESS FREE BOUNDARY CONDITIONS ON THE TOP AND BOTTOM SURFACES OF THE PLATE. THE PRESENT THEORY OBVIATES THE NEED OF SHEAR CORRECTION FACTOR. GOVERNING EQUATIONS AND BOUNDARY CONDITIONS OF THE THEORY ARE OBTAINED USING THE PRINCIPLE OF VIRTUAL WORK. THERMAL STRESSES AND DISPLACEMENTS FOR ORTHOTROPIC, TWO-LAYER ANTISYMMETRIC, AND THREE-LAYER SYMMETRIC SQUARE CROSS-PLY LAMINATED PLATES SUBJECTED TO COMBINED LINEAR AND NONLINEAR SINGLE SINUSOIDAL THERMAL LOAD ARE OBTAINED. THE VALIDITY OF PRESENT THEORY IS VERIFIED BY COMPARING THE RESULTS WITH THOSE OF CLASSICAL PLATE THEORY AND FIRST ORDER SHEAR DEFORMATION THEORY AND HIGHER ORDER SHEAR DEFORMATION THEORY.